2014
DOI: 10.1016/j.bbadis.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite disrupts brain mitochondrial energy homeostasis and induces mitochondrial permeability transition pore opening via thiol group modification

Abstract: Sulfite oxidase (SO) deficiency is biochemically characterized by the accumulation of sulfite, thiosulfate and S-sulfocysteine in tissues and biological fluids of the affected patients. The main clinical symptoms include severe neurological dysfunction and brain abnormalities, whose pathophysiology is still unknown. The present study investigated the in vitro effects of sulfite and thiosulfate on mitochondrial homeostasis in rat brain mitochondria. It was verified that sulfite per se, but not thiosulfate, decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…There are several proposed mechanisms by which elevated sulfite leads to neurotoxicity and clinical symptoms 2 . In vitro studies implicate sulfite accumulation in oxidative stress, disturbances of brain mitochondrial energy homeostasis and mitochondrial permeability transition pore opening resulting in neuronal damage characteristic of ISOD 12,13 . Lens dislocation is speculated to occur as a result of reduced levels of cystine (weakening the zonule of the lens) or secondary to elevated sulfites (causing disruption of cysteine disulphide bonds) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several proposed mechanisms by which elevated sulfite leads to neurotoxicity and clinical symptoms 2 . In vitro studies implicate sulfite accumulation in oxidative stress, disturbances of brain mitochondrial energy homeostasis and mitochondrial permeability transition pore opening resulting in neuronal damage characteristic of ISOD 12,13 . Lens dislocation is speculated to occur as a result of reduced levels of cystine (weakening the zonule of the lens) or secondary to elevated sulfites (causing disruption of cysteine disulphide bonds) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of SO deficiency and molybdenum cofactor deficiency, the levels of sulfite and sulfo derivatives of amino acids, proteins, and various compounds are increased in urine [21,24]. SO deficiency also results in the accumulation of sulfite in various tissues, especially in the brain [81]. However, the molecular mechanisms involved are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that excess sulfite might damage mitochondrial function via disruption of membrane integrity [9,84]. In rat brain, mitochondrial sulfite induced a decrease in ATP synthesis and disturbance of mitochondrial energy homeostasis [9,81]. In neurons and human fetal liver cells, it has also been shown that ATP is depleted due to sulfite toxicity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, B. wadsworthia has been associated with gut inflammation in various mice models with implications for the host sulfur metabolism (Devkota et al, 2012;Natividad et al, 2018). Moreover, sulfite is a known neurotoxin affecting brain mitochondrial energy homeostasis (Grings et al, 2014), and its increase reduces brain cell glutathione levels (Zhang et al, 2004). Accordingly, we observed reduced blood glutathione levels in the follow-ups of the PD patients ( Figure 2B).…”
Section: Sulfur Metabolism Is Changed In Pd-associated Gut Microbial mentioning
confidence: 99%